Toxoplasma infection and Rhesus blood group system: A systematic review and meta-analysis. - Tooran Nayeri; Mahmood Moosazadeh; Abdolhossein Dalimi Asl; Fatemeh Ghaffarifar; Shahabeddin Sarvi; Ahmad Daryani (PLoS ONE, 2023)
Background Toxoplasmosis is one of the most common infections in humans and animals, which is caused by an obligate intracellular opportunistic parasite known as Toxoplasma gondii (T. gondii). Some data have shown that both Rhesus (Rh)-positive and Rh-negative individuals differ in response to biological factors, including Toxoplasma infection. Therefore, this systematic review and meta-analysis was conducted to investigate the scientific evidence regarding the possible association between the Rh blood group and Toxoplasma infection and to determine the seroprevalence of T. gondii in the Rh blood group system. Methods The research was conducted on PubMed, ScienceDirect, ProQuest, and Google Scholar databases until January 2023. Twenty-one cross-sectional studies were included with a total of 10910 people. The data were synthesized using a random effect model with 95% confidence intervals (CIs). Results The overall prevalence of T. gondii was calculated at 32.34% (CI 95%: 28.23-36.45%) and 33.35% (CI 95%: 19.73-46.96%) in Rh-positive and Rh-negative blood groups. In addition, the pooled OR for the relationship between the Rh blood group and the seroprevalence of T. gondii was 0.96 (95% CI: 0.72-1.28). Conclusions This meta-analysis showed a high prevalence of Toxoplasma infection in both Rh-negative and positive blood groups. This systematic review and meta-analysis revealed that no significant association was found between toxoplasmosis and Rh factor. Because of the limited number of studies in this field, more research is recommended to determine the exact relationship between toxoplasmosis and the Rh factor.